Penegakan Hukum Pidana Terhadap Kegiataan Pertambangan Tanpa Izin - Novi Yanti Sandra Tutuarima; Deassy Jacomina Anthoneta Hehanussa; Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This article discusses the enforcement of criminal law against mining activities without a permit that transports mercury/mercury without a permit.Purposes of the Research: The purpose of this article is to discuss law enforcement against mining activities without permits and mining and types of criminal acts in the mining sector. Methods of the Research: The type of research used in this research is normative juridical According to Johnny Ibrahim, normative legal research is a scientific research procedure to establish truth based on scientific logic from the normative side. The normative side here is not limited to laws and regulations.Results of the Research: Still found mining activities without permission in this case the case I met which has come to the court decision where convict narwati Djahiri with a verdict (Number 378 / Pid.B-LH / 2020 / PN. Ambon). There was an arrest by Polairud because he was found transporting mercury / mercury in the waters between Buru island and Ambalau island without a permit from the government.